Kombinasi Metode Pijat Woolwich dan Massage Rolling (Punggung) Memengaruhi Kecukupan ASI pada Ibu Post Partum - Hastuti Usman (Jurnal Bidan Cerdas, 2019)
One of the failures of exclusive breastfeeding is the lack of a mother's level of confidence that her mother's milk cannot fulfill her baby's nutritional needs. Efforts that can be made to stimulate the hormone prolactin and oxytocin in the mother after childbirth is to provide a relaxed sensation in the mother by doing Woolwich massage and rolling massage (back). The purpose of this study was to determine the effect of a combination of Woolwich massage methods and Rolling Massage on Adequacy in postpartum mothers. Research site in the Work Area of Mapane Health Center, Poso Regency. The type of research used was Quasi-Experimental. Data analysis was performed by the chi square test. The results of the study showed that 95.8% of the intervention group respondents had enough baby weight while in the group without intervention it was 70.8% with a value of p = 0.048. Frequency of BAK: 87.5% of respondents in the intervention group had sufficient frequency while in the group without intervention it was 45.8% with a value of p = 0.006. BAB frequency in the intervention group 100% frequency is sufficient while in the group without intervention is 91.7% with a value of p = 0.015. This research is expected to be applied by midwives and taught to mothers and families to increase ASI production so that the coverage of exclusive breastfeeding is achieved in the area of the Research Health Center.